Kepuasan Pasien di Fasilitas Pelayanan Kesehatan (MJ Health) Johor Bahru, Malaysia - Nisaa, Arifatun; Noor, Ahmad Fariz Bin Mohd; Peng, Chong Lik (Politeknik Negeri Jember, 2025)
Although Johor Bahru offers a variety of healthcare services, including both public and private hospitals, there are still differences in patients' perceptions of the quality of care received. Several factors, such as waiting time, accessibility, medical facilities, healthcare professionals' skills, and communication between patients and medical staff, can influence patient satisfaction. This is particularly relevant to MJ Health, where no previous surveys have been conducted to assess patient satisfaction. Therefore, this study aimed to analyze patient satisfaction levels regarding healthcare quality at MJ Health Johor Bahru and identify the key factors contributing to their satisfaction. A quantitative approach was used, employing a questionnaire distributed to 250 respondents between February and July 2023. The findings indicate that staff professionalism (X3) has the most significant impact on patient satisfaction, with β = 0.35, p < 0.01. Given this result, hospitals are advised to conduct regular evaluations through patient satisfaction surveys to identify areas for service improvement and enhance overall healthcare quality.